Profit-Loss Sharing Financing and Stability of Indonesian Islamic Banking - Agus Widarjono; Zhafira Mardhiyah (Faculty of Islamic Economics and Business of UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
The study analyzes the extent to which Profit-Loss Sharing (PLS) financings with some control variables influence the stability of Islamic banks. Because of different scheme financings between Musharakah and Mudarabah, we also split them. This study measures stability utilizing Z-score. We employ the Autoregressive distributed lag (ARDL) model using monthly aggregate data of Islamic banks, covering from 2010:M1 to 2019:M12. This study is among studies who are pioneer in analyzing the role of PLS financing on stability. The findings shows that the PLS financings strengthen Islamic banks' stability for which Musharakah financing enhances the stability but Mudarabah financing weakens stability. Evidence also underlines that bank capital adequacy ratio (CAR) support stability but non-performing financing (NPF) and inefficiency lower stability. Macroeconomic conditions persistently support stability for which economic upturn fortifies stability but sharp depreciation weakens stability. This study implies that, in addition to Murabahah, Islamic banks have to diversify their financing on Musharakah.